2010
DOI: 10.1303/aez.2010.593
|View full text |Cite
|
Sign up to set email alerts
|

A multi-species pheromone lure: A blend of synthetic sex pheromone components for two mirid species, Stenotus rubrovittatus (Matsumura) and Trigonotylus caelestialium (Kirkaldy) (Heteroptera: Miridae)

Abstract: Two mirid bugs, Stenotus rubrovittatus (Matsumura) and Trigonotylus caelestialium (Kirkaldy) (Heteroptera: Miridae), are sympatric pests that infest rice in many regions of Japan. Three components, hexyl butyrate, (E)-4-oxohex-2-enal and (E)-hex-2-en-1-yl butyrate, in S. rubrovittatus and three other components, hexyl hexanoate, (E)-hex-2-en-1-yl hexanoate and octyl butyrate, in T. caelestialium, were identified as sex attractant pheromone components in these species. The synthetic pheromone lures for S. rubro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Combining the sex pheromones of multiple elaterid species in a single trap lure to monitor or mass trap populations of co‐occurring elaterids is of interest to farmers. This strategy has been tested in integrated pest management programmes for other insect taxa, such as cerambycid beetles (Fan et al, 2019; Hanks et al, 2018; Rice et al, 2020; Sweeney et al, 2014), moths (Brockerhoff et al, 2013; Knight et al, 2014; Preti et al, 2020), true bugs (Kim et al, 2015; Yasuda et al, 2010) and mealybugs (Sullivan et al, 2023; Waterworth et al, 2011). As a key feature of such a lure, the pheromone for each species must express the same level of attractiveness as it would in a single pheromone lure.…”
Section: Discussionmentioning
confidence: 99%
“…Combining the sex pheromones of multiple elaterid species in a single trap lure to monitor or mass trap populations of co‐occurring elaterids is of interest to farmers. This strategy has been tested in integrated pest management programmes for other insect taxa, such as cerambycid beetles (Fan et al, 2019; Hanks et al, 2018; Rice et al, 2020; Sweeney et al, 2014), moths (Brockerhoff et al, 2013; Knight et al, 2014; Preti et al, 2020), true bugs (Kim et al, 2015; Yasuda et al, 2010) and mealybugs (Sullivan et al, 2023; Waterworth et al, 2011). As a key feature of such a lure, the pheromone for each species must express the same level of attractiveness as it would in a single pheromone lure.…”
Section: Discussionmentioning
confidence: 99%
“…Traps with the multiple species pheromones were as effective as traps with a single pheromone for each pest. It is reported that the mixed and the combined lures could be useful as simultaneous monitoring tools for two sympatric major rice pests using a single trap (Yasuda et al, 2010). Brockerhoff et al (2013) stated that multiple-species trapping with a single trap has several advantages compared with single species trapping with single traps; requirement of fewer traps, saving labor and time to install traps and to check trap catches, reduction of diagnostic effort, and ultimately reduction of costs.…”
Section: Discussionmentioning
confidence: 99%
“…Double‐sided sticky boards (24 × 30 cm, Sankei Chemical, Kagoshima, Japan) with synthetic pheromone lures (Yasuda et al . ; Mochizuki et al . ; Yasuda et al .…”
Section: Methodsmentioning
confidence: 99%